The effect of human resources management practices on employee performance in public universities / Muhammad Adib Adam - Adam, Muhammad Adib (Faculty of Business and Management, 2019)
Achieving some standard of performance is the objective of all organizations because through these performances, organizations are able to grow and progress. Employee must understand his or her role in the organization before the performance of that role can be fairly assessed. It is continuous process where managers and employees work together to plan, monitor and review an employee’s work objectives or goals and his or her overall contribution to the organization. This is how plans are converted into desired outcomes in the organizations. An effective human resource practice has become one of the most important things to achieve employee performance. The purpose of this research is to investigate the effect of human resource practices on employee performance. This study used quantitative method which researcher distributed 150 questionnaire to three public universities sector in Bandaraya Melaka which are University Teknologi Mara Kampus Bandaraya Melaka ( 83 employees), University Teknikal Malaysia (130 employees) and Kolej Profesional Mara Bandar Melaka (77 employees). The total population for all three organizations is 290. A total of 150 set of questionnaire were send but only were returned and only 137 set were fully answered and suitable for the use of this study. The results indicated that training and development, employee compensation, recruitment and selection and appraisal system have significant relationship with employee performance.